INVESTIGATION ON PRODUCING SINGLE-LAYER PARTICLEBOARD FROM BAMBOO WASTE AND COCOA POD HUSKS - Thi Kim Hong, Tang; Duy Linh, Nguyen (Journal of Forestry Science and Technology, 2020)
Agricultural residues are the potential sources for producing bio-composite. Cocoa pod husk (CPH) is a waste material from cocoa industry. The objective of this project is to investigate the feasibility of using cocoa pod husks and bamboo waste for manufacturing hybrid particleboard. Chemical compositions of CPH were determined based on TAPPI Standard Test Methods resulting the cellulose of 29%, hemicellulose of 30%, lignin of 28% and ash content of 9%. Singe-layer particleboards containing different CPH/bamboo particle ratios (16%, 20%, 30%, 40% and 44%) were made using various urea–formaldehyde (UF) resin ratios (2%, 3%, 6%, 9% and 10%). The results indicated that panels produced by using mixing ratio of CPH particles up to 30% with up till 6% UF resin fulfilled the required standard TCVN7754:2007 for modulus of rupture (MOR) and internal bond (IB). The optimal condition is 30.6% CPH particle and 8.1% UF resin obtaining the lowest thickness swelling (TS) 13.2%, the highest value of MOR and IB is 13.1 MPa and 0.33 MPa respectively. The investigations stated cocoa pod husks and bamboo waste as alternative raw materials are feasible for particleboard production.